Reflection of the events of the First World War in the awards systems of the Balkan states - Potrashkov, Sergey (Дриновський збірник, 2022)
The article examines the changes in the awards systems of the Balkan countries caused by the First World War. By the beginning of the war, each of the Balkan countries had its own reward system with its own history and traditions. Each included orders, medals and insignia for both military and civilian merit.During the war years, awards performed the following main functions: a state attribute, a symbol of independence and sovereignty, which acquired special significance in situations when the enemy occupied in whole or in part the national territory, and the armed forces were forced to operate outside of it; proper insignia, encouraging and mobilizing subjects to perform various tasks, both at the front and in the rear; commemorative symbol designed to remind about the war, its main events, efforts and sacrifices.During wartime, the appearance of already existing awards was changed accordingly the needs of the moment. Military awards were issued not on ordinary, but on special "military" ribbons, an additional accessory appeared in the form of swords attached to the insignia, etc. Finally, new awards were instituted. The rewards systems of the Balkan countries during the First World War as a whole fulfilled the role assigned to them as reward tools and state paraphernalia. In the latter capacity, orders and medals were used when awarding them to the allies. In most of the countries under consideration, there were no changes in the order groups, or theywere insignificant. This is explained by the circumstances of participation in the war of each of the country. Award systems were replenished mainly with medals and crosses close to them in status, which appeared after the war, designed to preserve the memory of it and addressed to a wide range of people. It should also be noted that awards for various kinds of humanitarian activities are widespread in the countries under consideration.